Analisis Hukum Persaingan Terhadap Penyelenggaraan BUMN Berdasarkan Konsep Doktrin “Single Economic Entity” - Istiyanti, Erni (Sanskara Hukum dan HAM, 2024)
The relationship between one company and its subsidiaries or other companies can be referred to as a single economic entity. The lack of freedom of the subsidiary causes the subsidiary to become a single economic entity. The impact of a single economic entity is that the behavior of each subsidiary is considered to be the same. This research aims to examine two things, First, the legal relationship between the parent and subsidiaries with regard to the concept of "single economic entity", especially with regard to the assets of BUMN that come from directly separated state assets; Second, the legal responsibility of the state as a shareholder in the event that there are indications of non-independence of BUMN subsidiaries that can lead to violations of Law No. 5/1999. This research method uses normative research methods with literature study methods. The results of this research show: First, the state becomes acta de jure gestionis (jus gestionis) meaning that the state can be held accountable in the general judicial body. The state or government will lose its immunity as the holder of state sovereign authority (iure imperi) if the State is involved in a business affair. Second, the financial accountability of BUMN is subject to Law No.40 /2007 concerning Limited Liability Companies, namely accountability at the RUPS of the state as a shareholder who has included its capital in a persero is only responsible for the amount of capital that has been included and the assets of the persero are separate from state finances.